Does risk disclosure matter for trade credit? - Issal Haj-Salem; Khaled Hussainey (Journal of Risk and Financial Management, 2021)
In this paper, we examine the impact of risk disclosure practices on trade credit. We hypothesize that risk information could reduce information opacity that arises between companies and their suppliers. We collected annual reports for Tunisian listed companies for the period 2008-2013. This gives us 146 firm-year observations. We find that risk disclosure has a positive impact on the level of trade credit. Our paper offers a new empirical evidence on the role of risk disclosure in reducing information asymmetry and increase companies' access to short-term external funds. Our study provides managerial implications for firms, suppliers, and regulatory authorities.
Keywords: 330; content analysis; risk disclosure; trade credit; Tunisian listed companies